Aerothermoelastic flutter analysis and active vibration suppression of nonlinear composite laminated panels with time-dependent boundary conditions in supersonic airflow. (March 2018) - Chai, Yuyang; Li, Fengming; Song, Zhiguang; Zhang, Chuanzeng
Aerothermoelastic flutter properties of nonlinear composite laminated panels in supersonic airflow are studied, and investigations on active flutter and aerothermal postbuckling suppression for the panels with time-dependent boundary conditions are also carried out using macro fiber composite actuator and sensor. The von Karman strain–displacement relation in conjunction with the supersonic piston theory is applied in structural modeling. Nonlinear dynamic equations of motion for the structural system are established using Hamilton's principle and the assumed mode method. Frequency- and time-domain methods are used to investigate the aerothermoelastic characteristics and active flutter and aerothermal postbuckling suppression of the panels. Effects of aspect ratio and ply angle on the nonlinear aerothermoelastic behaviors are studied. The displacement feedback control is used to conduct the active flutter and postbuckling suppression. The nonlinear output controller consisting of a linear quadratic regulator and a nonlinear state estimator of extended Kalman filter is also used in designing the controller. Controlled vibration responses of the structural system under the two different controllers are compared. The results show that the developed linear quadratic regulator/extended Kalman filter controller is more effective than the displacement feedback control controller in flutter and postbuckling control of the panels with time-dependent boundary conditions in supersonic airflow.